Effects of scoparone on non-alcoholic fatty liver disease revealed by RNA sequencing - Huang, Xiaoyan; Gao, Ya; Cao, Houkang; Li, Jun; Mo, Siyi; Li, Ting; Wu, Jianzhao; Guo, Kai; Wei, Riming; Zhang, Kefeng (Frontiers in Endocrinology, 2022)
Scoparone (SCO) is known to have curative effect of alleviating liver injury. The purpose of this study was to observe the therapeutic effect and possible mechanism of SCO against high-fat diet (HFD) induced non-alcoholic liver disease (NAFLD) through in vivo experiments and RNA sequencing. Male Kunming mice were fed with HFD for 8 weeks to establish a mouse model of NAFLD, and SCO was used to treat NAFLD. Histopathology and biochemical indicators were used to evaluate the liver injury and the efficacy of SCO. RNA sequencing analysis was performed to elucidate the hepatoprotective mechanism of SCO. Finally, the differentially expressed genes of cholesterol synthesis and fatty acid (triglyceride) synthesis pathways were verified by quantitative real-time polymerase chain reaction (qRT-PCR) and western blot. The histopathological results showed that HFD could lead to significant steatosis in mice, while SCO could alleviate liver steatosis remarkably in NAFLD mice. The determination of biochemical indicators showed that SCO could inhibit the increased serum transaminase activity and liver lipid level induced by HFD. RNA sequencing analysis of liver tissues found that 2742 and 3663 genes were significantly changed by HFD and SCO, respectively. SCO reversed the most of genes involved in cholesterol synthesis and fatty acid (triglyceride) metabolism induced by HFD. the results of the validation experiment were mostly consistent with the RNA sequencing. SCO alleviated liver injury and steatosis in NAFLD mice, which may be closely related to the regulation of cholesterol and fatty acid (triglyceride) metabolism.